LAW ENFORCEMENT OF PETROLEUM EXPLOITATION IN THE BATANG HARI DISTRICT THAT IS WITHOUT A COOPERATION CONTRACT - M. Nanda Setiawan (Kanun Jurnal Ilmu Hukum, 2022)
The community in Batang Hari Regency exploits petroleum without a cooperation contract by drilling a well and then taking the oil contained in the well. This is one of the issues arising from oil and gas mining in Indonesia. This study aims to determine how law enforcement can be used to combat illegal petroleum extraction in Batang Hari Regency. This research employed a descriptive-analytical research design and an empirical legal methodology. According to research findings, the Batang Hari Police in the Batang Hari District implements preventative and punitive law enforcement measures that are quite effective at reducing the number of annual cases. Without a cooperation agreement, these actions target illegal petroleum exploitation. The law in Batang Hari Regency prohibits the exploitation of petroleum without a cooperation contract, which includes difficulty to access sites of illicit oil wells and the participation of individuals.